THE RELATION ANALYSIS OF MARKETING MIX AND CUSTOMER PURCHASE OF COFFEE IN MALABAR MOUNTAIN CAFÉ IN BOGOR CITY - Ernalsalia Ateta; Ketut Budi Susrusa; Gede Mekse Korri Arisena (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
The aims of this research are finding out the correlation between product and consumer purchasing decisions, price and consumer purchasing decisions, promotion and consumer purchasing decisions, place and consumer purchasing decisions. This research has already done form May until July 2020. The samples were 50 respondents taken by nonprobability sampling technique. Data were collected by questionnaires. Data analysis were descriptive analysis technique and Spearman’s Correlation analysis using SPSS 23 software. The results of this research shows the product is strongly related with the correlation coeffecient value positive, which means it has a directional correlation and product has a significant correlation with the consumer purchasing decision at Malabar Mountain Cafe in Bogor. The price is strongly related with the correlation coeffecient value positive, which means it has a directional correlation and price has a significant correlation with the consumer purchasing decision at Malabar Mountain Cafe in Bogor. The promotion is strong enough related with the correlation coeffecient value positive, which means it has a directional correlation and promotion has a significant correlation with the consumer purchasing decision at Malabar Mountain Cafe in Bogor.  The place is very weakly related with the correlation coeffecient value negative, which means it has undirectional correlation and the place has not a significant correlation with the consumer purchasing decision at Malabar Mountain Cafe in Bogor.